The Classification of Prospective Students with Rapid Miner - Agus Sifaunajah; Riesca Dewi Wahyuningtyas (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
The application of information systems in various daily life processes results in data accumulation. Classification is a process in data mining to perform data analysis to generate models to describe the classes contained in the data. In this study, the ID3 Algorithm was used to classify prospective student data. This research employed a qualitative research model using the rapidminer tool application to carry out the classification process. Processed data is data obtained from surveys through google form media. The results of this study showed a classification model using the Interactive Dichotomizer Algorithm (id3), which can be developed into an information system for the admission of prospective students. It also revealed that data classification of students